Intellectual Capital, Non-Performing Loan, and Inflation’s Effects on Firm Value : The Mediating Role of Financial Performance - Agustina Dian Putri Manurung; Isfenti Sadalia; Syahyunan (Mutiara: Multidiciplinary Scientifict Journal, 2023)
This paper aims to analyze how financial performance can mediate the influence of intellectual capital, non-performing loans and inflation on firm value. Our sample is 39 banks in Indonesia that have passed the criteria based on purposive sampling, with a total of 5 years of observation. This research is quantitative research with a panel data multiple regression model, which will be processed using E-views and a Sobel test calculator to test the mediation effect. The findings of this research show that VACA, VAHU, non-performing loans and inflation have a direct effect on financial performance. However, STVA has no effect. Also directly, VACA, non-performing loans and financial performance influence firm value. However, VAHU, STVA and inflation have no effect on firm value. The results of the Sobel test succeeded in proving that financial performance was able to mediate the influence of VACA, VAHU, non-performing loans and inflation on firm value. However, it failed to prove the mediating influence of financial performance on STVA and firm value.